Representasi Pola Asuh Otoriter Dalam Film “Nanti Kita Cerita Tentang Hari Ini”: Sebuah Kajian Deskriptif - Dzakiy Muhammad Alfadhil; Silviana Purwanti; Johantan Alfando WS; Dony Kristian (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Film, as a form of mass communication media, not only reflects social reality but also shapes public understanding of communication patterns within families. Nanti Kita Cerita Tentang Hari Ini (NKCTHI) portrays an authoritarian parenting style that is closely associated with patriarchal culture in Indonesia and may affect children’s psychological well-being. This study therefore examines how authoritarian parenting is represented in the film and how such meanings are interpreted by audiences. This research employs a descriptive qualitative method using Stuart Hall’s representation analysis through encoding and decoding processes. The focus is on the depiction of authoritarian parenting in NKCTHI, analyzed through scenes, dialogue, gestures, and cinematic techniques, with data collected from observation and literature review. The findings indicate that NKCTHI represents authoritarian parenting across eleven scenes, characterized by high demands, low warmth, punitive approaches, absence of negotiation, and limited trust in children. The encoding process is evident in the visual elements, dialogue, and gestures of the father as a dominant figure. Meanwhile, the researcher’s decoding position falls within the negotiated code, as the father is also portrayed with moments of warmth. The film suggests that the impact of parenting is shaped more by communication patterns within the family than by rules alone.